Pengaruh Musik Klasik Terhadap Hasil dan Aktivitas Belajar Matematika Siswa Kelas VII di SMPN 2 Kota Bengkulu - Prakoso, Yans Al; Hannifah, Hannifah; Maizora, Syafdi (JP2MS, 2017)
This research aimed to know The Influence of Classical Music to Activity and Learning Mhatematic Achievement for Student’s Grade VII in SMPN 2 Bengkulu City. This is a quasi-experimental research which use pree-test and post-test design. The population in this research is the student’s grade VII in SMPN 2 Bengkulu City. There are 276 respondents. The sampling technique that is used is purposive sampling. This research is got 34 respondents for every class. The data analysis that is used is t-test. To activity, the result of the study shows that the score of activity with an avarage is in interval  with criteria is good. And to learning Achievment, the result of the study shows that the score of t-end = 0.1012  t-table = 1.99656.  From the result of study above we can conclude that there is an influence on classical music to ativity for student’s grade VII in SMPN 2 Bengkulu City and there is no an influence on classical music to learning mhatematic achievement for student’s grade VII in SMPN 2 Bengkulu City. Key words : Classical Music, Activity, and Learning Mhatematic Acievement.